Strong presidents and grand corruption scandals in the Philippines - Eric V.C. Batalla (Public Administration and Policy)
Purpose – This paper provides evidence from the Philippines that strong presidents (termed here as hyper-presidents) have failed to address systemic corruption despite their anti-corruption rhetoric and promises. Design/methodology/approach – The paper uses a case study methodology to review how “strong presidents” have dealt with the problem of corruption in the Philippines and to examine their handling of grand corruption scandals. Data were collected from court decisions, congressional reports, news reports, journal articles, and other academic publications. Findings – The paper has two major findings. First, none of the strong presidents were able to build the social and political foundations for anti-corruption reform. Second, in dealing with corruption scandals, the strong presidents observed selective persecution and particularistic concealment (cover-ups) instead of allowing the rule of law to prevail. These findings dismiss the idea of the sufficiency of strong presidents, some of whom project the possession of the political will necessary to combat corruption in the country. Originality/value – While the need for strong leaders has been emphasized in the anti-corruption literature, this paper argues that such leaders do not necessarily add to the political commitment needed to fight systemic corruption or even lay the political, institutional, and social foundations for reform. Strong presidents in the weak Philippine state are powerless against the institutions and culture that encourage and tolerate grand corruption.